Investigating the Feasibility of FPGA-based Network Switches - Meng, Jiuxi; Gebara, Nadeen; Ng, Ho-Cheung; Costa, Paolo; Luk, Wayne (IEEE 30th International Conference on Application-specific Systems, Architectures and Processors (ASAP), 2019)
FPGAs are being increasingly used on network interface cards (NICs) as offload units to accelerate packet processing tasks. The rationale is that by customizing the NIC logic it is possible to achieve higher performance for the most critical tasks while eliminating unnecessary logic, thus improving overall efficiency. In this paper, we aim to investigate if similar benefits can also be extended to network switches. We compare different switch architectures and analyze their suitability to an FPGA implementation. We discuss several optimization techniques to overcome the challenges of limited FPGA resources and assess the scalability of our designs up to 10, 25, and 50 Gb/s throughput per port.